Low geriatric nutritional risk index as a poor prognostic biomarker for immune checkpoint inhibitor treatment in solid cancer - Zhang, Lilong; Wang, Kunpeng; Kuang, Tianrui; Deng, Wenhong; Hu, Peng; Wang, Weixing (Frontiers in Nutrition, 2023)
Objective In this investigation, we focused on the geriatric nutritional risk index (GNRI), a comprehensive metric that takes into account the patient’s ideal weight, actual weight, and serum albumin levels to measure malnutrition. Our primary objective was to examine the predictive value of GNRI-defined malnutrition in determining the response to immunotherapy among cancer patients. Methods Relevant articles for this study were systematically searched in PubMed, the Cochrane Library, EMBASE, and Google Scholar up to July 2023. Our analysis evaluated overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and disease control rate (DCR) as clinical outcomes. Results This analysis comprised a total of eleven articles encompassing 1,417 patients. The pooled results revealed that cancer patients with low GNRI levels exhibited shorter OS (HR: 2.64, 95% CI: 2.08–3.36, p < 0.001) and PFS (HR: 1.87, 95% CI: 1.46–2.41, p < 0.001), and lower ORR (OR: 0.46, 95% CI: 0.33–0.65, p < 0.001) and DCR (OR: 0.42, 95% CI: 0.29–0.61, p < 0.001). Sensitivity analyses confirmed that the above results were stable. Egger’s and Begg’s tests revealed that there was no publication bias in the above results. Conclusion Our results imply that the GNRI is a useful predictor of immunotherapy response in cancer patients.